The Impact of Productive Zakat on Improving the Welfare ofMustahik Micro EnterprisesAt the National ZakatAmil Agency (BAZNAS) Parepare City - Rachman, Mawaddah; Semaun, Syahriyah; Suarning, Suarning; Mahsyar, Mahsyar; Zubair, Muhammad Kamal (Jurnal Ar-Ribh, 2024)
This  researchaimsto  analyze  the  methods  and  effect  of  effective  zakat  on  improving  the  welfare  of  mustahik  micro  groupsat  the Parepare metropolis country  wide  Zakat  Amil  organization.  This  studieschanged  intoexecuted  to  BAZNAS  leaders  to  find  outproductive  zakat  tactics,  even  as  to  mustahik  to  find  out  the  impact  on  improving  the  welfare  of  mustahik  micro-firms.  by  way  ofusing  qualitative  studiesmethods  and  subjectresearchtypes,  as  well  asthe  use  of  a  case  take  a  look  atresearchtechnique.  The statisticsobtainedmay  be  concluded  that  commercial  enterprise  capital  from  effective  zakat  given  to  mustahik  can  enhance  the  welfare  of  mustahik  micro-businesses.  the  extent  of  mustahik  welfare  is  seen  from  al-Ghazali's  approach,  particularly  welfare  primarily  based  on  ad-Diin,  an-Nafs,  al-Aql,  an-Nahl,  and  al-Mall.